Feasibility and safety of early initiation of a PCSK9 (proprotein convertase subtilisin/kexin type 9) inhibitor in patients with acute myocardial infarction undergoing primary PCI. (25th November 2020) - Okada, T; Tsushima, R; Taya, S; Saito, E; Takagi, W; Sogo, M; Ugawa, S; Nosaka, K; Takahashi, M; Okawa, K; Sakane, K; Miyoshi, T; et al.
Abstract: Background: Recent ESC/EAS Guidelines for the management of dyslipidemia stated that the treatment goal of LDL cholesterol (LDL-C) in very high-risk patients is less than 55mg/dl. PCSK9 inhibitors in addition to strong statins could be a useful strategy for rapid and aggressive lowering of LDL-C. However, the feasibility and safety of early initiation of a PCSK9 inhibitor for AMI patients undergoing primary PCI remain unclear. Objectives: We examined the effects of early initiation of a PCSK9 inhibitor, evolocumab, on lipid profile and inflammatory markers and its safety in AMI patients undergoing primary PCI. Methods: This study is a single center, randomized, controlled trial involving 102 patients hospitalized for AMI. The patients were randomly assigned 1:1 to the evolocumab group and the control group. Evolocumab (140 mg) was subcutaneously injected within 24 hours after PCI and then every two weeks. All patients received pitavastatin (2mg/day) in addition to the allocated treatment. The primary endpoints were changes in lipid profile and inflammatory markers from baseline to 4 weeks. Results: 102 patients were enrolled between October 2017 and December 2019. 89 patients were ST-segment elevation myocardial infarction (STEMI), 13 patients were non-STEMI. Primary PCI was successfully performed in all patients. 76 patients were statin-naïve. 2 patients were excluded from analyses because they died severe heart failure in acute phase. Finally, 100 patients (evolocumab; n=51 and control; n=49) were analyzed. Baseline LDL-C was 121.6±30.3 mg/dl in the evolocumab group and 124.7±33.6 mg in the control group. Change in LDL-C from the baseline to 4 weeks was −92.4±32.4 mg/dl (−75%) in the evolocumab group and −44.8±32.1 mg/dl (−33.1%) in the control group (mean difference; 47.6mg/dl, 95% CI; 34.8 to 60.4 mg/dl, p<0.001). LDL-C <70mg/dl at 4 weeks was achieved in 96.0% of the evolocumab group as compared with 26.5% of the control group. Further, in the evolocumab group. LDL <55mg/dl was achieved in 92.1% at 2 weeks and 92.1% at 4 weeks. Regarding inflammatory markers, there were no significant difference in change in high-sensitivity C-reactive protein (p=0.49) and tumor necrosis factor-alpha (p=0.63) between two groups even after adjustment of baseline value. No adverse event associated with evolocumab was observed during this study. Conclusion: In patients with AMI undergoing primary PCI, early initiation of evolocumab rapidly reduced LDL-C without no adverse event, and achieved LDL-C<55mg/dl in most patients within 2 weeks. Early administration of a PCSK9 inhibitor combined with a strong statin could be a feasible and safe treatment for AMI patients undergoing PCI. Funding Acknowledgement: Type of funding source: None